PENGARUH MODEL PEMBELAJARAN ADVANCE ORGANIZER BERBANTUAN MEDIA DART BOARD TERHADAP KEMAMPUANBERPIKIR KRITIS SISWA PADA MATERI LAJU REAKSI - Zona Octarya (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research aimed at seeing the effect of Advance Organizer (AO) learning model with Dart Board media toward student critical thinking ability on Reaction Rate lesson at the eleventh grade of Natural Science of Islamic Integrated Senior High School of Al-Ittihad Pekanbaru. It was a quasi-experimental research with pretest-posttest design. The subjects of this research were the eleventh-grade students of Natural Science in the Academic Year of 2019/2020. Purposive sampling technique was used in this research, so there were 2 sample classes—the eleventh-grade students of Pa Natural Science (experimental group) and the students of Pi Natural Science (control group). The data were collected through observation, preliminary data test that was homogeneity test, and final data tests that were pretest and posttest. Independent sample t-test with SPSS 21 was used to know and analyze the effect of AO learning model with Dart Board media toward student critical thinking ability. Based on the result of processing the final data, it was obtained that the score of Sig. (2-tailed) 0.000 was lower than 0.05 (0.000<0.05). It could be concluded that Ha was accepted and H0 was rejected. It showed that there was an effect of AO learning model with Dart Board media toward student critical thinking ability at the eleventh grade of Natural Science of Islamic Integrated Senior High School of Al-Ittihad Pekanbaru. To know the effect of AO learning model with Dart Board media toward student critical thinking ability, it was done the calculation of determination coefficient (r2), and it was obtained the coefficient of effect 54.43%.